Examining the Relationship Between Teachers' School Climate and Their Attitudes Towards School Bullying (Journal of Management and Educational Sciences, 2024)
This study aimed to examine the relationship between teachers' perceptions of school climate and their attitudes towards school bullying. The research was carried out with the relational screening model. According to the results of the research; it is seen that the teacher attitudes towards school bullying of the teachers who participated in the research are below average and their perceptions of school climate are above average. The fact that teacher attitudes towards school bullying are below average can be said that teachers are sensitive to school bullying and they do not allow bullying in schools. The fact that school climate perceptions are above average can be said that the working environment in the schools they work in is a democratic learning environment suitable for education and training. In the examination according to gender; male teachers' attitudes towards school bullying were higher than female teachers. On the other hand, school climate perceptions do not change according to women and men. In the examination according to marital status; teachers' attitudes towards school bullying and their perceptions of school climate do not change according to their married and single status. In the examination according to educational status; teachers' attitudes towards school bullying and their perceptions of school climate do not change according to their undergraduate and graduate education. In the examination according to age groups; teachers' attitudes towards school bullying and perceptions of school climate do not change according to age groups. In the examination according to service year groups; perceptions of school bullying of teachers with 6-10 years of service were found to be higher than teachers with 11 years of service and above. Finally, there is a low-level, significant and negative relationship between teachers' attitudes towards school bullying and perceptions of school climate. In addition, teachers' perceptions of school climate significantly predict teachers' attitudes towards school bullying. Accordingly, a 100-unit increase in the success factors sub-dimension of teachers' school climate reduces school bullying behavior by 23.1%. Again, a 100-unit increase in the conflict sub-dimension of teachers' school climate reduces school bullying behavior by 15.3%.